Valorisation du rôle anti-staphylococcique chez les Pseudomonas spp. fluorescents isolés à partir des racines d’une plante graminée sauvage. - MOUMENE, Nadjette (My University, 2021)
Some bacteria generally in biofilm are said to be persistent to denote their ability to survive high doses of antibiotics. They become persistent by slowing their growth, a bit as if they were going into "hibernation" to protect themselves from antibiotic treatments. Among these microbes we find Staphylococci which are bacteria involved in various pathologies and of varying degrees of severity. They are one of the primary agents responsible for nosocomial and community infections. Treatments to eradicate infections are difficult because many strains are multi-resistant. For this, it is important to find valid alternative therapeutic strategies. As part of this work, two strains of Staphylococcus aureus were collected: one isolated from the nasal cavity and the other from the educational microbiology laboratory. They were identified based on phenotypic identification tests including the API STAPH gallery. In an attempt to resolve this diffuse disorder, a study of the anti-staphylococcal effect of some fluorescent Pseudomonas was carried out. 26 Pseudomonas isolates were selected from bacteria obtained from three samples of roots of wild grasses. Four isolates were used in the inhibition of two strains of Staphylococcus aureus by applying the cross-streak method on Mueller Hinton medium and King B medium. The best performing Pseudomonas in this antagonism test were identified via biochemical tests and physiological to determine their species. The results show that the latter are likely to belong to the species Pseudomonas fluorescens. Of the four isolates of Pseudomonas, two inhibited the growth of target Staphylococci. This inhibitory activity was obtained on King B medium and not on Mueller Hinton medium. The best performing isolate P21 inhibited both strains of Staphylococcus "SI" and "SH" with zones of inhibition of 9mm and 17mm respectively. This indicates that the metabolite which caused this inhibition may be pyoverdin, which act by depletion of the medium. The results of the extraction and characterization of pyoverdins deserve more time to be confirmed by replicates.
Keywords: Staphylococcus aureus - infections - antibiotics - Pseudomonas - pyoverdines